Upaya Meningkatkan Mutu Pendidikan Melalui Pengelolaan Kurikulum dan Pembelajaran - Alifia, Fadilla (PEMBELAJAR: Jurnal Ilmu Pendidikan, Keguruan, dan Pembelajaran, 2024)
Education is a way to change. As we know, from time to time education has always been a problem that will never be resolved until an indefinite time. Given that we need to make changes and always improve along with the current situation. The efforts to improve the quality of education are often discussed by the experts based on their own perspectives. And according to the author himself, one way to improve the quality of education is through curriculum management and learning. Therefore, what kind of curriculum and learning management can improve the quality of education?